Perindopril and a Galectin-3 Inhibitor Improve Ischemic Heart Failure in Rabbits by Reducing Gal-3 Expression and Myocardial Fibrosis - Li, Sha; Li, Shuren; Hao, Xiao; Zhang, Yuehua; Deng, Wenhao (Frontiers in Physiology, 2019)
Objective: Ventricular remodeling is considered the basis of heart failure and is involved in myocardial fibrosis. This study aimed to assess perindopril and a galectin-3 inhibitor (modified citrus pectin, MCP) for their effects on ventricular remodeling and myocardial fibrosis in rabbits with ischemic heart failure. Methods: Rabbits were divided into sham, heart failure (model), MCP, and perindopril groups, respectively. A rabbit model of ischemic heart failure was established by ligating the anterior descending coronary artery. Then, the rabbits were orally administered MCP, perindopril, or saline (all at 2 ml/kg/d) for four weeks. Sham animals only underwent open heart surgery without further treatment. After 4 weeks, cardiac function was examined by ultrasound, and myocardial Gal-3, collagen type I, and collagen type III expression was assessed, at the gene and protein levels, by real-time PCR and Western-Blot, respectively; serum Gal-3 was detected by ELISA, and fibrosis in the infarct zone was evaluated by H&E and Masson staining. Results: In model animals, myocardial Gal-3, collagen type I, and collagen type III gene and protein expression levels were increased compared with control values, as well as serum Gal-3 amounts. Treatment with perindopril and MCP significantly alleviated the above effects, with no significant differences between the treatment groups. Pathological analyses showed that compared with model animals, treatment with MCP or perindopril resulted in relatively neatly arranged myocardial cells in the infarct zone, with significantly decreased fibrosis. Conclusion: Perindopril and the galectin-3 inhibitor MCP comparably improve ischemic heart failure in rabbits, by downregulating Gal-3 and reducing myocardial fibrosis.